Horizontal ridge augmentation using GBR with a native collagen membrane and 1:1 ratio of particulate xenograft and autologous bone: A 3‐year after final loading prospective clinical study. (8th July 2019) - Meloni, Silvio Mario; Jovanovic, Sascha Alexander; Urban, Istvan; Baldoni, Edoardo; Pisano, Milena; Tallarico, Marco
Abstract: Background: Cawood‐Howell class IV atrophies, also known as "knife‐edge" ridges, represent a serious horizontal defect, making the placement of regular implants challenging. Aim: To clinically and radiographically evaluate bone regeneration of severe horizontal bone defects with 3 years of follow‐up. Materials and Methods: This study was designed as a single cohort, prospective clinical trial. Patients having horizontal bone width of 4 mm or less in the posterior mandible or maxilla were treated with resorbable collagen membranes and a 1:1 mixture of anorganic bovine bone (ABB) and autogenous bone. Implants were inserted and loaded 7 months later. Outcomes were implant and prosthetic survival rates, any biological and prosthetic complications, horizontal and volumetric bone dimensional changes measured on cone beam computer tomography (CBCT), peri‐implant marginal bone level (MBL) changes measured on periapical radiographs, plaque index (PI), and bleeding on probing (BOP). Results: Eighteen patients received 55 implants. No patient dropped‐out. No implant and prosthetic failures and no complications were recorded. Super imposition of pre and 7‐month postoperative CBCT scans revealed an average horizontal bone gain of 5.03 ± 2.15 mm (95% CI: 4.13‐5.92 mm). After 3 years, mean MBL was 1.15 ± 0.28 mm (95% CI 0.84‐1.22 mm). The PI was 11.6%, and BOP was 5.2%. Conclusion: Within the limitations of the present study, high implant survival rate and high average bone augmentation seem to validate the use of collagen resorbable membranes with a 1:1 mixture of particulate ABB and autogenous bone for the reconstruction of Cawood‐Howell class IV alveolar ridge atrophies.